Extending the knowledge system and food value of kumala (lpomoea batatas or sweetpotato) in Vanuatu as a response to climate change : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Horticultural Science at Massey University, Manawatū, New Zealand - Setak, Patricia (Massey University, 2018)
Loss of traditional knowledge in food production is a major problem occurring in many countries due to modernization and globalization. Additionally, further compelled by the impacts of climate change, this can have a devastating effect on the livelihood of people. As a result, farmers are therefore compelled to revive the use of traditional knowledge in food production especially its blended use with contemporary knowledge in adapting to and mitigating climate change impacts. The aim of this study is to identify the contribution of traditional knowledge of kumala (Ipomoea batatas) production in sustaining the livelihoods of people in Vanuatu. The target population of this study was kumala farmers in two villages: Lorevulko and Sara 1 in East Santo, Vanuatu where qualitative data using semi-structured interviews was obtained. A literature review was also undertaken on kumala production in other countries where kumala is commonly grown. The younger generations should be educated on traditional knowledge and skills, and efforts should be made to document traditional knowledge. Traditional knowledge is being used in the pre-production activities of kumala such as planting calendar, site selection, land clearing and soil preparation. Both knowledge systems are used in the production of kumala for example in kumala cultivar selection, division of labour, planting, crop maintenance, preparation and management of kumala during droughts and cyclones. In addition, both traditional and contemporary knowledge are used in post-production of kumala in different storage methods such as field, bag, basket, and food bed. Overall, the findings in this study confirm compelling evidence that traditional knowledge contributes towards the sustainable livelihood of the people in Lorevulko and Sara 1. It shows that there is an assimilation of knowledge systems and they create a cultural output that is unique to location and time, and provides a good example of cultural dynamics which never stand still and which respond to environmental and other pressures. Findings from this research will contribute immensely in improving food security at the household and national level in Vanuatu, and generate sustainable income for farmers and livelihoods for farmers. Researchers can also use the findings of this study as a basis to undertake further studies on traditional knowledge of kumala in Vanuatu. Moreover, the results will be useful for informing and influencing government policy and farming practices.
Figures 3 & 4 and Appendices 6 & 7 were removed for copyright reasons but may be accessed via their source listed in the References.
Keywords: Sweet potatoes; Vanuatu; Traditional farming; Sweet potato industry; Food security; Climatic factors